Acute renal failure in patients with severe falciparum malaria. - Trang, T; Phu, N; Vinh, H; Hien, T; Cuong, B; Chau, T; Mai, N; Waller, D; White, N (1992)
Since 1988 in this referral center for severe cases of malaria for South Vietnam, a specialist team has managed malaria-associated renal failure (MARF) with peritoneal dialysis, and the mortality rate of MARF has fallen from 75% (78 of 104) to 26% (27 of 104) (P < .0002). Sixty-four patients with MARF (of whom 12 died) were compared to 66 patients with severe malaria whose serum creatinine levels remained < 250 mumol/L (six died). MARF had the clinical and biochemical features of acute tubular necrosis and was significantly associated with liver dysfunction (P < .05). A fatal outcome was associated significantly with anuria, a short history of illness, multisystem involvement, and high parasitemia. Most patients died from complications related to renal failure. Recovery of renal function was unrelated to parasitemia or hemoglobinuria; the median (range) time until urine output exceeded 20 mL/(kg.d) was 4 (0-19) days, and the time (mean +/- SD) for serum creatinine level to return to normal was 17 +/- 6 days. MARF can be managed effectively by prompt and careful peritoneal dialysis, but more effective dialysis or diafiltration might reduce the mortality rate further.